Association of tobacco with hypertension in adult females: Evidence from National Family Health Survey-IV for an aspirational Indian state - Sushree Priyadarsini Satapathy; Smita Kumari Panda; Prakash Chandra Panda; Kulwant Lakra; Sadhu Charan Panda; Priyanka Dhawan; Sonu Goel (Elsevier, 2022)
Background: Elevated blood pressure and tobacco consumption have been the top two causes of preventable mortality worldwide. Females in the reproductive age carry a higher health impact for self and the offspring when exposed to one or both these risks. An in-depth assessment of the sociocultural determinants of hypertension and tobacco usage in an aspirational Indian state like Odisha is carried out through secondary analysis of the National Family Health Survey-IV (NFHS-4) dataset. Methods: Data of 30,587 women aged between 15 and 49 years were extrapolated for analysis through frequency, percentage and logistic regression model to determine the predictors of tobacco use and hypertension and to correlate the two in the study population. Results: In Odisha, 12.8% adult women were addicted to tobacco, mostly smokeless form (93.3%). High blood pressure was recorded in 7.3% of the respondent females. Increasing age, urban residence, extremes of wealth index, ever married status, obesity, diabetes, and tobacco usage (more for smokeless) were the predictors of hypertension. Education, caste and occupation had no significant associations. Conclusion: Targeted interventions involving gender, marital status, obesity, residence and other socio-economic profiles may be adopted for risk reduction of non-communicable diseases like hypertension in the reproductive age females.